Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Get the answers you need quickly and accurately from a dedicated community of experts on our Q&A platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.

Solve the system by substitution.

-9y - 10 = x

5x+ 6y = -11


Sagot :

Step-by-step explanation:

-9y - 10 = x

x = -9y - 10

5x + 6y = -11

5(-9y - 10) + 6y = -11

-45y - 50 + 6y = -11

(-45 + 6)y = -11 + 50

-39y = 39

y = 39/-39

y = -1

x = -9y - 10

x = -9(-1) - 10

x = 9 - 10

x = -1